The Contribution of Cement Companies to the Achievement of Sustainable Development Goals and its Effect in Building Trust in their Communities - Adriana Martínez Lecuona; Manuel González Pérez; Paola Selene Vera Martínez; Genoveva Rosano Romero; Martín Badillo Maldonado (European Scientific Journal, ESJ, 2017)
Companies have reoriented their actions in contributing towards the attainment of the Sustainable Development Goals (SDGs). The SDGs enhances the reputation of enterprises and builds confidence in their stakeholders. People's confidence toward the company generates favorable attitudes and behaviors. Therefore, the purpose of this paper is to identify the level of contribution of cement companies to achieve Sustainable Development Goals and its effect on the trust of its local communities. In achieving the purpose of this work, we study the perception of people about the actions that the company makes in favor of sustainable development. The study variables correspond to 9 of 17 SDGs classified into two categories (people and environment). The nine variables are compared with confidence. Data are also analyzed with statistical standardization and chi-square tools. The results show that only 40% of the actions carried out by the company contribute to the achievement of the SDGs. However, there is no significant relationship between the population's confidence in the company and the actions that the firm makes in favor of sustainable development.